Dynamics of Pesantren Formation: The Origins of Pesantren and Institutional Growth - Purwanti Purwanti; A Andari; MA Ansori; Febryan Hadinata (Journal of Social Research, 2023)
Law No. 20 of 2003 on the national education system emphasizes the purpose of national education to form individuals of faith, piety, noble character, and knowledge. Pesantren also has a dual role as a translator of Islamic teachings and as a traditional educational institution that maintains moral values in the times. This study aims to determine the origin of pesantren and institutional growth. The method used is the literature study method with a qualitative approach. The results of this study show that the origin of pesantren and the institutional growth of pesantren in Indonesia originated from a simple practice where individuals who mastered Islamic religious knowledge began to teach their knowledge to the surrounding community. Over time, pesantren became an important Islamic educational institution in the history and development of Indonesia. Pesantren have a variety of types, from very traditional to very modern, reflecting the diversity in Islamic education systems and approaches in Indonesia.